Pengaruh motivasi, sikap, dan persepsi konsumen terhadap pemilihan lembaga Arva School of Fashion di Surabaya - Ajeng Lailil Ismiar Rosida (STIE Perbanas Surabaya, 2017)
The increasing business competition can lead to consumer behavior in deciding to buy a product. In addition, with the development of the era of technology with its more sophis-ticated and dynamic implementaion, the companies are demanded quickly and appror-paite to decide anything so as not to compete with other companies. This study aims to examine the effect of consumer behavior that includes consumer motivation, consumer attitudes, and perceptions of the decision of the selection of Arva School of Fashion Sura-baya. The population in this study were students and alumni of the Arva School of Fa-shion Surabaya with a sample of 130 respondents who—on average—they lived around Surabaya. The analysis used a descriptive analysis and multiple linear regression analy-sis to test consumer motivation, consumer attitudes, and significant perceptions both simultaneously and partially on the decisions of students and alumni to choose Arva School of Fashion Surabaya. The results of statistical tests show that the variables of consumer motivation, consumer attitudes, and perceptions jointly influence the decision to choose Arva. In addition, consumer motivation, consumer attitudes, and perceptions partially have a significant effect on the choice of Arva.